Use of ozone therapy in wound healing: Case report (Research, Society and Development, 2025)
Ozone, a gas composed of three oxygen atoms (O₃), has been widely studied and applied as a complementary therapy in veterinary medicine due to its bactericidal, virucidal, fungicidal, immunomodulatory, and wound-healing effects, in addition to improving blood circulation and tissue oxygenation. This study aimed to report and evaluate the effectiveness of ozone therapy associated with allopathic treatment in the healing of traumatic wounds in a dog that was a victim of a car accident. It is a descriptive, qualitative case report involving a six-year-old female Standard Poodle that presented with extensive and difficult-to-heal lacerations in the right hind limb. Treatment included surgical debridement, antibiotic therapy, analgesia, anti-inflammatories, and mineral supplementation, combined with ozone therapy using the bagging technique and topical application of ozonized coconut oil. Ten ozone therapy sessions were performed, with doses adjusted according to clinical evolution, documented through medical records, imaging exams, and photographic records. The results showed a progressive reduction of the inflammatory process, formation of viable scar tissue, and gradual wound closure in a shorter period, without adverse effects. The association between conventional therapy and ozone therapy significantly improved vascularization, infection control, and wound healing. It is concluded that ozone therapy is an effective tool as an integrative treatment for complex wounds in dogs, standing out as a safe, easy-to-handle, and promising method in veterinary clinical practice, contributing to faster patient recovery.